Systems biology of asphalt pollutants and their human molecular targets - Rozewski, Eran; Taqi, Omran; Fini, Elham H.; Lewinski, Nastassja A.; Klein-Seetharaman, Judith (Frontiers in Systems Biology, 2023)
More than 90% of all the roads in the USA are covered in asphalt, despite hundreds of scientific studies demonstrating the detrimental effect of asphalt on human health. Why is asphalt not banned from use? The answer to this question is at least in part due to the fact that asphalt is not one compound, but a complex mixture of thousands of compounds. Here, we not only review studies of the effects of asphalt on human health, but go a step further by taking a novel view of these health effects from a systems biology perspective. In particular, we propose an analogy to protein protein interaction networks, which can be within species and across species when looking at host-pathogen interactions. While in the former, all nodes are of the same type (e.g. human proteins), in the latter nodes can be of different types, such as human proteins and pathogen proteins. To build a corresponding network of interactions between different nodes, we retrieved the literature studying the molecular targets of identified components in asphalt and their corresponding cellular biomarkers. Using this approach, we show that a complex trans pollutant-human target network appears in which multiple health effects can be triggered through interactions of multiple pollutant molecules with multiple human targets. We envision that the insights gained from this analysis may assist future efforts at regulating the use of asphalt.